The Nutritional Education Effect Of Healthy Snacks With Quartet Card Media Toward Elementary School Students’ Nutritional Knowledge - yuli laraeni; I Nyoman Adiyasa; Lalu Khairul Abdi; Risma Widianti (Jurnal Gizi Prima (Prime Nutrition Journal), 2023)
Background: The students at school age are categorized into a risky period toward health problems. The health condition of students at elementary school affects the student's achievements. The education on nutrition given to them effectively shifts toward healthy eating behavior. Some efforts were made to provide nutrition education for elementary school-aged children through attractive media to support accessible materials conveyed. One engaging medium that is "attractive" to children as a medium of instruction is the quartet card.Objective: To analyze the effect of nutritional education on healthy snacks using a quartet card as the media to improve elementary students' nutrition knowledge. Research Methods: The research method used in this study is a literature study by finding the supporting theoretical references relevant to the study. The data used in this study were secondary data obtained from journals, documentation books, and the internet in the last five years with the keywords healthy snacks, elementary school children, and quartet cards. The collected data were then analyzed according to a descriptive qualitative research method Research Result: The results of the study found a significant effect on the student's knowledge of nutrition using quartet cards in which the elementary school students, in fact, significantly achieve the goals of conducting nutritional education efforts. Conclusion: The quartet card media is quite effective in increasing the knowledge of elementary school children because it can increase children's attention, concentration, and imagination. Then the child is expected to start learning to apply what is known so that, in the end, it can form good knowledge. In addition, the quartet card media also has a role as a learning medium designed to convey messages through the images presented in it.